Pengembangan Bahan Ajar Bahasa Indonesia untuk Penutur Asing Bertema Kuliner Lokal Tulungagung - Abidah, Zayyin; Maulida, Siti Zumrotul (Hiski Malang, 2021)
The teaching materials is importat in the learning process, especially in Indonesian language for foreign speakers (BIPA). The teaching materials can be used as a learning resource and to reduce the learners’ cultural shock. Culinary is the culture that is integrated into BIPA teaching materials, which is developed at the A1 level with the theme of Tulungagung local culinary. They are presented in an interesting, interactive, effective, and easy to be used in everyday life. The research and development of teaching materials refers to the Borg and Gall models. The results of the study are obtained from the scores of the feasibility analysis of teaching materials and response tests as well as verbal data in the form of written data, such as comments, criticisms, and suggestions from material experts, media experts, and foreign learners. In the first stage, the feasibility test results of teaching materials received 82.69%, meaning that teaching materials can be used with improvement. In the second phase of the feasibility test, teaching materials got 98.56%. Furthermore, the foreign learner response test reached 89%. Thus, the BIPA textbook with the theme of local tulungagung culinary is worthy to use, and included in the valid category.